Epidemiology investigation and analysis of patients with hemodialysis in Sichuan province of China. (1st January 2019) - Zou, Yang; Hong, Daqing; He, Qiang; Wen, Yu; Li, Guisen
Abstract: Objectives: To investigate the incidence, pathogenesis, as well as mortality rate and causes of end-stage renal disease patients with hemodialysis (ESRD-HD) in Sichuan province of China. Methods: In this retrospective descriptive study, all the data were exported from the Chinese National Renal Data System (CNRDS). The demographic and pathogenic information from 01 January 2011 to 31 December 2016 were statistically analyzed. Results: According to the data from CNRDS, the incidence of ESRD-HD was high in Sichuan province. From 2011 to 2016, the annual incidence rate of ESRD-HD was 61.84, 73.75, 78.04, 66.04, 72.61, and 60.98 per million population (pmp). Male ESRD-HD patients were higher than female patients (1.5:1). The major causes of ESRD-HD in Sichuan province from 2011 to 2016 were chronic glomerulonephritis and diabetic nephropathy. The annual mortality rate of ESRD-HD was 113.20, 91.25, 73.02, 68.56, 68.57, and 58.39 per 1000 person-years. The descending rate of mortality was parallel in both males and females. The mortality rate was observed to be higher in the elderly group (age ≥ 60). The major cause of mortality was cardiovascular diseases (24.48%). Conclusions: In Sichuan province, the incidence of ESRD-HD annually was gradually descending. The elderly and male patients had higher incidence of ESRD-HD. The annual mortality rate of ESRD-HD was declining year by year, and elderly patients aged ≥ 60 contributed to the highest mortality rates. The major cause of death was cardiovascular diseases. This could contribute to a better understanding of ESRD-HD in southwest of China, thus providing better treatment for ESRD in the future.